Functional MRI Preprocessing in Lesioned Brains: Manual Versus Automated Region of Interest Analysis - Garrison, Kathleen A.; Rogalsky, Corianne; Sheng, Tong; Liu, Brent; Damasio, Hanna; Winstein, Carolee J.; Aziz-Zadeh, Lisa S. (Frontiers in Neurology, 2015)
Functional magnetic resonance imaging has significant potential in the study and treatment of neurological disorders and stroke. Region of interest (ROI) analysis in such studies allows for testing of strong a priori clinical hypotheses with improved statistical power. A commonly used automated approach to ROI analysis is to spatially normalize each participant’s structural brain image to a template brain image and define ROIs using an atlas. However, in studies of individuals with structural brain lesions such as stroke, the gold standard approach may be to manually hand-draw ROIs on each participant’s non-normalized structural brain image. Automated approaches to ROI analysis are faster and more standardized, yet are susceptible to preprocessing error (e.g., normalization error) that can be greater in lesioned brains. The manual approach to ROI analysis has high demand for time and expertise but may provide a more accurate estimate of brain response. In this study, we directly compare commonly used automated and manual approaches to ROI analysis by reanalyzing data from a previously published hypothesis-driven cognitive fMRI study involving individuals with stroke. The ROI evaluated is the pars opercularis of the inferior frontal gyrus. We found a significant difference in task-related effect size and percent activated voxels in this ROI between the automated and manual approaches to ROI analysis. Task interactions, however, were consistent across ROI analysis approaches. These findings support the use of automated approaches to ROI analysis in studies of lesioned brains, provided they employ a task interaction design.